(untitled) (Scientific journal of the Fergana State University, 2023)
The article describes the features of the use of virtuality ideas in social sciences. Virtuality and its possibilities in the study of existence are also considered in detail. It has been studied that a more effective approach to the study of virtuality in modern science can be implemented on the basis of a synthesis of elements of all existing methodological approaches, in particular: dialectical, informational, systemic, synergetic, etc.